Attitudes towards economic risk and the gender pay gap - Anh T. Le; Paul W. Miller; Wendy S. Slutske; Nicholas G. Martin (Institute for the Study of Labor (IZA), 2010)
This paper examines the links between gender differences in attitudes towards economic risk and the gender pay gap. Consistent with the literature on the socio-economic determinants of attitudes towards economic risk, it shows that females are much more risk averse than males. It then extends this research to show that workers with more favorable attitudes towards risk are associated with higher earnings, and that gender differences in attitudes towards economic risk can account for a small, though important, part of the standardized gender pay gap.
Keywords: J31; J71; 330; wages; gender; risk; wage gap